2020
DOI: 10.1038/s41415-020-1250-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral splints for temporomandibular disorder or bruxism: a systematic review

Abstract: This systematic review comprehensively summarised the best available evidence from randomised controlled trials on the effects of oral splints for temporomandibular disorders (TMD) and bruxism.There is no evidence to support the use of oral splints for either condition based on the results found.For TMD patients, sensitivity analyses were conducted to explore the effects of differences in: 1) diagnostic criteria; 2) splint types; and 3) outcome measures used and reported. There were no differences in the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…Previous reviews such as the 2007 systematic review by the Cochrane Collaboration [2] found insufficient evidence to affirm the use of occlusal splints in bruxism therapy. A recent systematic review published during editing of the present review had similar findings and did not find evidence to support splint use for temporomandibular disorders or bruxism [3].…”
Section: Introductionsupporting
confidence: 53%
“…Previous reviews such as the 2007 systematic review by the Cochrane Collaboration [2] found insufficient evidence to affirm the use of occlusal splints in bruxism therapy. A recent systematic review published during editing of the present review had similar findings and did not find evidence to support splint use for temporomandibular disorders or bruxism [3].…”
Section: Introductionsupporting
confidence: 53%
“…Riley et al 59 in an SR on the use of OD for TMD or bruxism concluded that “the body of evidence that this conclusion is based on is of very low certainty. The studies included in this review differed in three important factors: (1) diagnoses, (2) splint type, and (3) outcome measurement/reporting.…”
Section: Occlusal Devices (Od)mentioning
confidence: 99%
“…The use of occlusal splint therapy has been shown to reduce pain intensity and increase maximal mouth opening [ 48 ]. However, whether the effect of an occlusal splint is due to the placebo effect has been questioned, and that the evidence of its efficacy remains to be low [ 49 , 50 ]. A systematic review in 2018 by Alkhutari et al has suggested that the use of occlusal splint may improve patient-centred treatment outcomes, which may be more than merely a placebo effect [ 51 ].…”
Section: Treatment Modalities—a Change In Paradigm?mentioning
confidence: 99%